STRATEGI KOMUNIKASI GURU DALAM MENUMBUHKAN RASA EMPATI SISWA REGULER DI LINGKUNGAN PENDIDIKAN INKLUSIF (Studi Kasus pada Sekolah Kreatif SD Muhammadiyah 16 Surabaya) (Universitas Negeri Surabaya, 2023)
Inclusive education is increasingly being applied to both private and public schools. So it is increasingly important for parents and teachers to educate and teach students to have empathy to prevent unwanted things. Creative School SD Muhammadiyah 16 Surabaya is one of the schools that always strives to teach empathy to its students so that learning is always conducive. This research was conducted using constructivism paradigm, case study method, and qualitative approach. The purpose of this study was to determine the communication strategies carried out by teachers in fostering empathy of regular students in students with special needs in the inclusive education environment of the Creative School SD Muhammadiyah 16 Surabaya. This study was conducted by interviews and observations on teachers, regular students, and parents. The results of this study show that the most successful communication strategy in fostering empathy of regular students in students with special needs is to see and model the attitudes shown by teachers and make rewards as motivation to do good things in the environment, especially students with special needs.